Garang: Medium Transfer Materi Folklor dan Aktivitas Lokal Masyarakat Pegunungan - Putra, Muhammad Ade; Resyad, Mohammad; Rahmat, Al Fauzi (Umbara, 2023)
This study aims to explore the folklore and social dynamics at Pandansari Village, focusing particularly on Embel Hamlet. This study employs observational methods, in-depth interviews, and literature review. The research finds that Pandansari villagers often share folklore and engage in social activities during gatherings known as Garang, typically held in the warmth of their kitchens with family members. Garang serves as a conduit for transmitting cultural narratives and social customs, fostering a deeper understanding of the moral values upheld by farmers in nurturing familial and societal bonds. Furthermore, this study underscores the significance of local wisdom embodied in folklore and social practices such as Telaga Ranjeng, Gua Jepang, Tuk Bening, gamelan, and Ratiban at Pandansari Village. Shedding light on these aspects, this paper contributes to our comprehension of folklore and social dynamics prevalent in mountain communities, enriching our collective knowledge.